CHARACTERIZATION OF TEMPORAL VARIABILITY IN NEAR-SURFACE SOIL MOISTURE AT SCALES FROM 1 H TO 2 WEEKS - Parent A.-C.; Anctil F.; Parent L.-E. (My University, 2006)
This study proposes a characterization of the temporal relations between soil moisture and precipitation at a very short time-scale, i.e. from 1 h to 2 weeks. The analysis is based on seven soil moisture time series from time domain transmission (TDT) probes positioned along a 90-m transect, and monitored at a 20-min rate in the shallow soil layer (5-25 cm), and on precipitation observed every 15 min. Wavelet analysis is proposed for the characterization of the temporal relationships between soil moisture and precipitation. The normalized local wavelet spectrum of soil moisture reveals power features related to the precipitation events in the short scales, and residing in the long scales. The variance activity depicted in the wavelet power spectra of precipitation and soil moisture is organized in preferential bands of wavelet scales: 1-48 h, 48 h to 1 week, and 1-2 weeks. For the 1-48 h scale, soil moisture is linked to precipitation occurrence, intensity and duration, while for the 48 h to 1 week scale soil moisture relates to the periodicity of the rainfall events, and for the 1-2 weeks scale to the duration of the dry spells. Additionally, a distance-time wavelet analysis was conducted to simultaneously assess spatial and temporal variabilities for each of the three predefined bands. The spatial analysis showed many similarities between series along the transect that were attributable to soil homogeneity. The averaging of the variance showed that 93% of the concentration of the precipitation variance was at the 1-48 h scale, while most of the soil moisture variation (85%) was accounted for at the 48 h to 2 weeks scale. Disparity between the short duration of precipitation system and the extension of the soil moistening process is due to the transfer of energy from precipitation to soil moistening. © 2006 Elsevier B.V. All rights reserved.
Keywords: SOIL MOISTURE; TEMPORAL VARIABILITY, PRINCIPAL COMPONENT ANALYSIS; WAVELET ANALYSIS